GINGIVAL RECESSION TREATMENT BY TUNNELING, PLATELET-RICH FIBRIN MEMBRANE, DOUBLE CROSS SUTURE WITH BELT-SUSPENDERS TECHNIQUE - PRITIA, MARDHA ADE; MURDIASTUTI, KWARTARINI (International Journal of Applied Pharmaceutics, 2025)
Objective: Gingival recession by treating tunneling technique can minimize flap opening so that obtain more adequate blood supply. The addition of a platelet-rich fibrin (PRF) membrane enhances the healing process due to the presence of growth factors. Apart from that, the double cross suture combined with the belt and suspenders technique can also help the success of the treatment. Methods: A 30 y old female came in complaining her teeth had felt sore for the last 1 y. Complaints increased when brushing teeth and drinking cold drinks, especially on the upper right teeth. The etiology was due to an error in brushing teeth, resulting in gingival recession on teeth 13 of 1 mm and 15 of 2 mm (class 1 Miller). Alveolar bone did not decrease on radiographs. The initial treatment was done by scaling and polishing, followed by the application of desensitizing agents to reduce pain, the patient was instructed to replace her toothbrush type and trained with the modified Stillman method. The surgery used tunneling with PRF membrane, sutured by a double cross combined with the belts-suspenders technique. The controls were done after days 7, 14, 30, 90 and 120. Results: The results showed that gingival recession on teeth 13 and 15 was corrected 100% from 1 mm and 2 mm to 0 mm. After day 120, there were no complaints of pain or aches, and the patient was satisfied. Conclusion: The combination tunneling, PRF membrane, sutured by double cross combined with belts and suspenders technique could be an alternative treatment in cases of Miller class 1 gingival recession stable up to 120 d.